Putusan Mahkamah Konstitusi Nomor: 85/PUU-XX/2022 Tentang Badan Peradilan Khusus Sebagai Landmark Decisions - Fauzi, Wildan Muhhamad; Muslim, Ikhwanul; Alhadi, Muhammad Nurcholis (Bacarita Law Journal, 2025)
The Constitutional Court is a judicial institution responsible for maintaining law and justice through its decisions known as landmark decisions. One of the decisions that is currently controversial in society is Decision Number 85/PUU-XX/2022 concerning the establishment of a special judicial body that should have been formed before the regional head elections which will be held simultaneously in 2024. However, until now there has been no legal certainty regarding the establishment of a special judicial body and the Constitutional Court remains authorized to handle regional head election disputes. The purpose of this study is a form of examination to determine whether the Constitutional Court Decision Number 85/PUU-XX/2022 meets the criteria as a landmark decision or not as interpreted by the Constitutional Court. By using a qualitative approach, this study uses a normative legal analysis based on descriptive legal theory. The data sources used in this study are journals, books and the results of previous studies that have been published. The results of the discussion in this study indicate that the Constitutional Court Decision Number 85/PUU-XX/2022 successfully meets the four criteria for a landmark decision. However, there is one criterion that was not met, namely a decision that annulled the entire law because the panel of judges only annulled Article 157 paragraph (1), (2) and the phrase in Article 157 paragraph (3) so that this decision cannot be fully categorized as a landmark decision.